After Removal : The Choctaw in Mississippi - Tubby, Roseanna; Wells, Samuel J. (Book collections on Project MUSE., 1986)
This informative study helps to complete the saga of the Choctaw by documenting the life and culture of those who escaped removal. It is an account that until now has been left largely untold. The Choctaw Indians, once one of the largest and most advanced tribes in North America, have mainly been studied as the first victims of removal during the Jacksonian era. After signing the Treaty of Dancing Rabbit Creek in 1830, the great mass of the tribe--about 20,000 of perhaps 25,000--was resettled in what is present-day Oklahoma. What became of the thousands that remained? The history of the Chocta.